SPE/DOE Enhanced Oil Recovery Symposium 1992
DOI: 10.2118/24172-ms
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigations of Steam and Hot-Water Flooding in Fractured Porous Media

Abstract: Effective and economic recovery of oil from fractured reservoirs by steamflooding rely on thorough understanding of the physical process mechanisms. The objective of this research is to study steamflooding mechanisms in fractured porous media using laboratory experiments and mathematical modeling. The experimental results have been published previously [1-3]. A mathematical model developed for simulating laboratory coreflood results is presented in this paper. The model is a two-dimensional, three phase, therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Natural convection in fluid-saturated porous materials is encountered in many applications such as molten metals infiltration in porous media [9][10][11][12], drying and transport of gases in porous media [13][14][15], enhanced oil recovery by hot-water flooding in porous beds [16], combustion of heavy oils in porous reservoirs [17,18], etc., where the thermal boundary conditions play a significant role in the overall process. Effects of thermal boundary conditions, such as sinusoidal heating and discrete heating, are reported in the literature [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Natural convection in fluid-saturated porous materials is encountered in many applications such as molten metals infiltration in porous media [9][10][11][12], drying and transport of gases in porous media [13][14][15], enhanced oil recovery by hot-water flooding in porous beds [16], combustion of heavy oils in porous reservoirs [17,18], etc., where the thermal boundary conditions play a significant role in the overall process. Effects of thermal boundary conditions, such as sinusoidal heating and discrete heating, are reported in the literature [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that the rate of heat transfer between the matrix and the fractures, both by conduction and convection, plays an important role in oil recovery of the NFRs. Jensen et al 17 . developed a non‐isothermal three‐phase model using the finite difference method to analyze the data obtained by laboratory experiments for fractured domains.…”
Section: Introductionmentioning
confidence: 99%
“…Enhancement of oxygen transport in liquid metal by natural convection during oxidation of liquid lead and lead-bismuth eutectic in a discretely heated enclosure was investigated by Ma et al 37 Studies on natural convection in porous media due to discrete heat sources are mainly focused on electronic cooling applications. [38][39][40][41] However, thermal treatment of various fluids in porous media have several other important applications such as molten metal infiltration in porous media, [42][43][44][45] drying and transport of gases in porous media, [46][47][48] enhanced oil recovery by hot-water flooding in porous beds, 49 combustion of heavy oils in porous reservoirs, 50,51 etc. Thus, an understanding of the role of discrete heating for various fluids in porous media is important and such studies are yet to appear in the literature.…”
Section: Introductionmentioning
confidence: 99%